Studying the Effect of Adding Doekhla kaolin Clay and Alumina to Iraqi Bauxite on Some Physical and Mechanical and Thermal Properties - Abdul-Hamead, Alaa A. (Al-Khwarizmi Engineering Journal, 2019)
The aim of this work is to produce samples from Iraqi raw materials like Husyniat Bauxite (raw and burnt) and to study the effect of some additives like white Doekhla kaolin clays and alumina on that material properties were using sodium silica as a binding material. Five mixtures were prepared from Bauxite (raw and burnt) and kaolin clays, with an additive of (40) ml from sodium silica and alumina of (2.5, 5, 7.5,10 wt %) percentage as a binding material. the size grading was through sieving. The formation of all specimens was conducted by a measured gradually semi-dry pressing method under a compression force of (10) Tons and humidity ratio ranging from (5-10) % from mixture weight. Drying all specimens was done and then they were burnt under (1200)°C temperatures according to a burning program which raised the temperature (5)°C per minute and then the soaking interval. Some tests such as the physical, mechanical and thermal test were connected on the testing results for the specimens indicated that the raw materials with fine size range and high temperature gave specimens a thermal phase with higher percent of Mullit in comparison with coarse size. Bulk density values, coefficient of longitudinal and hardness increase with porosity and ratio of water absorption values decrease. Also, results show that Alumina with Bauxite gives it stiffens because of the increase of the mullite phase which is characterized by high mechanical and thermal properties especially thermal conductivity. Results show that the best thermal and mechanical properties are found in the fifth mixture (X5) which contains a ratio of about (10) % of Al2O3 .